If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -5)(2x + 8) = 0 Reorder the terms: (-5 + 3x)(2x + 8) = 0 Reorder the terms: (-5 + 3x)(8 + 2x) = 0 Multiply (-5 + 3x) * (8 + 2x) (-5(8 + 2x) + 3x * (8 + 2x)) = 0 ((8 * -5 + 2x * -5) + 3x * (8 + 2x)) = 0 ((-40 + -10x) + 3x * (8 + 2x)) = 0 (-40 + -10x + (8 * 3x + 2x * 3x)) = 0 (-40 + -10x + (24x + 6x2)) = 0 Combine like terms: -10x + 24x = 14x (-40 + 14x + 6x2) = 0 Solving -40 + 14x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-20 + 7x + 3x2) = 0 Factor a trinomial. 2((-4 + -1x)(5 + -3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(5 + -3x)' equal to zero and attempt to solve: Simplifying 5 + -3x = 0 Solving 5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667Solution
x = {-4, 1.666666667}
| (x+3)(x+3)=X^2+81 | | 456=(20+2x)(15+2x) | | 1+4(x-8)=4-5(x-1) | | x^2+y^2-6x+4y+6=0 | | 8n+14=2n-4 | | 9x+3y=167 | | 5(5+x)+10=5-5x | | 3x-10+x+14=160 | | 2x-1+6=11 | | 7y^2+4y= | | 6m+4(6m-4)=26-8(2m-12) | | 3x+6y=168 | | 2(x+7)-5(2x-6)=92 | | 12x^2+4x=-5 | | p+4p=15 | | 1=-16x^2+b | | 9x+6y=171 | | 4cos^2(x)=5-4sinx | | 9x+6y=170 | | x*20=2 | | 18=-16t^2+80t+18 | | log(4x+1)=log(25) | | (cozx-1)(cosx-2)=0 | | 3x^2+24x+3=0 | | 1+0.80a=2+0.75a | | 2(4x-9)=42 | | 5x=4+2y | | 0.05(7-x)+0.1x=0.56 | | log(6)(5x+4)=2 | | 6a^2-6a=0 | | 2(2y+8)-10=-30 | | 15+0.75a=13 |